REKONSTRUKSI KONSEP KONTRAK HIBRIDA DALAM HUKUM PERDATA INDONESIA: ANALISIS ANTARA FLEKSIBILITAS BISNIS DAN KEPASTIAN HUKUM - David Novan Setyawan; Zainal Arifin; Moch. Wahid Hasyim (Jurnal Magister Hukum Perspektif, 2026)
The development of the digital economy and the complexity of modern business transactions call for more flexible forms of contracts than the traditional ones found in the Civil Code. This phenomenon has given rise to the concept of hybrid contracts, namely agreements that combine several types of contracts into a single legal relationship. The purpose of this study is to analyze the legal basis of hybrid contracts in Indonesian civil law and to propose a conceptual reconstruction aimed at balancing business flexibility and legal certainty. The method employed is normative legal research using legislative, conceptual, and comparative approaches. The findings indicate that the principle of freedom of contract (Article 1338 of the Civil Code) provides legal space for hybrid contracts; however, the absence of clear normative boundaries creates potential uncertainty in legal enforcement. Conceptually, this article develops three reconstructive principles: (1) the principle of functionality, which prioritizes the economic purpose of the contract in interpretation; (2) the principle of proportionality, which limits freedom of contract to prevent structural imbalances; and (3) the principle of adaptive certainty, which demands that legal norms remain clear while remaining responsive to technological developments. Comparatively, the Dutch preponderance test and the “intention of the parties” approach in English common law are adapted as models for Indonesian judges. The findings indicate that the absence of formal interpretation guidelines leads to inconsistencies in case law. This study recommends the establishment of guidelines for interpreting hybrid contracts, minimum standard clauses for platform contracts, and reforms to the Civil Code that accommodate modern contracts as concrete steps toward an adaptive and equitable contract law ecosystem. Keywords: hybrid contract, civil law, business flexibility, legal certainty, freedom of contract